2015
DOI: 10.1002/gcc.22249
|View full text |Cite
|
Sign up to set email alerts
|

Integrated copy number and gene expression profiling analysis of epstein–barr virus‐positive diffuse large b‐cell lymphoma

Abstract: Viral oncogenes and host immunosenescence have been suggested as causes of Epstein-Barr virus-positive diffuse large B-cell lymphoma (EBV + DLBCL) of the elderly. To investigate the molecular genetic basis of immune evasion and tumor outgrowth, we analyzed copy number alterations (CNAs) and gene expression profiles in EBV + DLBCL samples compared with EBV - DLBCL. There were relatively few genomic alterations in EBV + DLBCL compared with those detected in EBV-negative DLBCL. The most frequent CNAs (>30%) in EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 52 publications
0
60
0
Order By: Relevance
“…These findings suggest that the host response to a viral infection in B cells had the most important impact on the transcriptomic signature of EBV þ PT-DLBCL. It is particularly interesting that EBV þ DLBCL of the elderly (EBV þ DLBCL-E), recently investigated by Yoon et al (32), bears GEP characteristics similar to EBV þ DLBCL. In addition, this rare lymphoma developing in individuals aged over 50 years without any known immunodeficiency (33) displayed several other characteristics overlapping with EBV þ PT-DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the host response to a viral infection in B cells had the most important impact on the transcriptomic signature of EBV þ PT-DLBCL. It is particularly interesting that EBV þ DLBCL of the elderly (EBV þ DLBCL-E), recently investigated by Yoon et al (32), bears GEP characteristics similar to EBV þ DLBCL. In addition, this rare lymphoma developing in individuals aged over 50 years without any known immunodeficiency (33) displayed several other characteristics overlapping with EBV þ PT-DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of EBV+ DLBCL, particularly in Asia, have shown an activated B cell (ABC)-like immunophenotype, which is consistent with the substantial NF-κB activation that was revealed by immunohistochemistry and gene expression profiles [4, 8, 1011]. NF-κB activation is a common feature that occurs through various mechanisms in ABC-DLBCL.…”
Section: Introductionmentioning
confidence: 61%
“…In our previous gene expression study we observed overexpression of downstream target genes of IL4 in EBV+ DLBCL [4]. CCL22, which is overexpressed in SLAMF1 high and CHOP-treated cells, recruits IL4-secreting Th2 cells [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations